2009
DOI: 10.1063/1.3077606
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced light extraction efficiency of GaN-based light-emitting diodes with ZnO nanorod arrays grown using aqueous solution

Abstract: We report a dramatic increase in the light extraction efficiency of GaN-based blue light-emitting diodes (LEDs) by ZnO nanorod arrays on a planar indium tin oxide (ITO) transparent electrode. ZnO nanorods were grown into aqueous solution at the low temperature of 90 °C. With 20 mA current injection, the light output efficiency of the LED with ZnO nanorod arrays on ITO was increased by about 57% with no increase in a forward voltage over the conventional LEDs with planar ITO. The increased light extraction by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…However, V 2 O 5 has hardly been considered as a candidate for light emitting due to the unsatisfying emission intensity. Recent papers reported that GaN based light emission diodes capped by ZnO layer or nanostructures showed enhanced light emission, which may provide an effective way to increase the light emission efficiency of luminescence materials [75], [76]. Thus it is interesting to investigate the light emission of V 2 O 5 /ZnO bi-layer composites in an effort to obtain enhanced light emission from ZnO incorporated V 2 O 5 nanostructures.…”
Section: Zno/v2o5 Bilayermentioning
confidence: 99%
“…However, V 2 O 5 has hardly been considered as a candidate for light emitting due to the unsatisfying emission intensity. Recent papers reported that GaN based light emission diodes capped by ZnO layer or nanostructures showed enhanced light emission, which may provide an effective way to increase the light emission efficiency of luminescence materials [75], [76]. Thus it is interesting to investigate the light emission of V 2 O 5 /ZnO bi-layer composites in an effort to obtain enhanced light emission from ZnO incorporated V 2 O 5 nanostructures.…”
Section: Zno/v2o5 Bilayermentioning
confidence: 99%
“…Extensive research efforts have been devoted to improving the light extraction from GaN-based LEDs by various approaches, including surface texturing, 1 patterned sapphire substrates, 2,3 reflectors, 4,5 photonic crystals, 6,7 nanopatterned surface 8,9 and flip-chip LEDs. 13,14 Influence of density of ZNAs on the light extraction efficiency was also experimental investigated. With vertical ZnO nanorods/nanotips grown on transparent p-electrode of GaN-LEDs by metal-organic chemical vapor deposition (MOCVD), 1.5 and 1.7 times enhanced light output power of GaN-LEDs compared with conventional GaN-LEDs were achieved, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This example shows that without changing the LED structure, by growing ZnO NRs it is easy to achieve higher-brightness LEDs. There were also reports about a dramatic increase in the light extraction efficiency of GaN-based blue LEDs by ZnO NRs arrays grown on a planar indium tin oxide (ITO)transparent electrode [31]. The light output efficiency of these LEDs was increased by about 57% with no increase in forward voltage over the conventional LEDs with planar ITO.…”
Section: Light Emitting Diodesmentioning
confidence: 99%